The relations between latin america and china: a focusing approach (2007)
This essay tends to provide an approach focus to the analysis of relations between Latin America and the Popular Republic of China (RPC) from an international studies perspective. The growing economic, diplomatic and military projection of China in the region deserves more detailed and solid research on its meaning and extent. Meanwhile, the study of Chinese-Latin American ties can not be performed without incorporating the impact of the United States on them.